QM-MM Approach to the Accurate Description of Slow Diffusion in Porous Materials - Trachta, Michal; Volny, Tomas; Rubeš, Miroslav; Bulánek, Roman; Bludsky, Ota (American Chemical Society, 2023)
A QM-MM methodology to improve the theoretical description of slow diffusion in microporous materials using ab initio data is presented. At a modest computational cost, the two-step ab initio correction to activation energy significantly enhances force field model performance. This approach was applied to the small hydrocarbons (C1- C3) diffusion through 8MRs (8-membered rings) in siliceous zeolites. The improved ab initio description of the hydrocarbon transition states in 8MRs leads to more systematic behavior of the method that captures the trends in experimental measurements. The proposed method may be broadly applied to a wide variety of systems for which empirical potentials of sufficient quality are not available.
QM-MM přiblížení k přesnému popisu pomalé difúze v porézních materiálech
Keywords: framework flexibility; modeling adsorption; silica zeolites; self-diffusion; lta zeolites; force-field; hydrocarbons; simulation; separation; transition; modelování adsorpce; zeolit; simulace; separace; samodifuze